2012
DOI: 10.1016/j.immuni.2012.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Activators Induce Interleukin-1α Secretion via Distinct Pathways with Differential Requirement for the Protease Function of Caspase-1

Abstract: Through their capacity to sense danger signals and to generate active interleukin-1β (IL-1β), inflammasomes occupy a central role in the inflammatory response. In contrast to IL-1β, little is known about how IL-1α is regulated. We found that all inflammasome activators also induced the secretion of IL-1α, leading to the cosecretion of both IL-1 cytokines. Depending on the type of inflammasome activator, release of IL-1α was inflammasome dependent or independent. Calcium influx induced by the opening of cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
259
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(282 citation statements)
references
References 45 publications
20
259
2
1
Order By: Relevance
“…Recent studies have shown that myeloid cells secrete IL-1␣ in response to many classical inflammasome activators (9,14). These responses are dependent on canonical inflammasome components and result in the cosecretion of IL-1␣ and cleaved IL-1␤; however, particulate NLRP3 activators also induced inflammasome-independent IL-1␣ secretion in one study (14).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies have shown that myeloid cells secrete IL-1␣ in response to many classical inflammasome activators (9,14). These responses are dependent on canonical inflammasome components and result in the cosecretion of IL-1␣ and cleaved IL-1␤; however, particulate NLRP3 activators also induced inflammasome-independent IL-1␣ secretion in one study (14).…”
mentioning
confidence: 89%
“…These responses are dependent on canonical inflammasome components and result in the cosecretion of IL-1␣ and cleaved IL-1␤; however, particulate NLRP3 activators also induced inflammasome-independent IL-1␣ secretion in one study (14). Even in the absence of IL-1␣ secretion, however, bioactive, surface-bound IL-1␣ is produced by monocytes solely in response to NF-Bactivating signals and does not require inflammasome components, caspase-1, or IL-1␤ (9).…”
mentioning
confidence: 94%
“…We and others previously suggested that S. pneumoniae cells internalized by macrophages underwent rapid death and released PLY, thereby destabilizing phagosomal membranes in a PLY-dependent manner (11,35). Interestingly, phagosomal destabilization by particulate NLRP3 activators has been proposed to facilitate the production of IL-1␣ independently of the inflammasome machinery (30). From those observations, it is also conceivable that PLY released from internalized pneumococci promotes IL-1␣ production through the destabilization of phagosomal membranes.…”
Section: Discussionmentioning
confidence: 90%
“…It was reported previously that several inflammasome activators induce the maturation and secretion of IL-1␣ in a manner dependent on inflammasome components, including ASC (apoptosis-associated speck-like protein containing a CARD [caspase activation and recruitment domain]) and caspase-1 (30)(31)(32)(33). We previously reported that in S. pneumoniae-infected macrophages, the AIM2 and NLRP3 inflammasomes play a critical role in caspase-1 activation and the subsequent processing and secretion of IL-18 and IL-1␤ (11).…”
Section: Resultsmentioning
confidence: 99%
“…4) is unclear, because this cytokine (and IL-18) is part of the IL-1 family that is also activated by the innate caspase-1 inflammasome complex (31). The reason may be that IL-1␤ activation and IL-1␣ activation require different pattern recognition "trigger"' signals or compartmentation strategies to feed their specific precursors into the inflammasome complex (32) or may involve other independent activation pathways (33), such as platelets which produce IL-1␤ (25).…”
Section: Discussionmentioning
confidence: 99%